A novel tri-layered photoanode of hierarchical ZnO microspheres on 1D ZnO nanowire arrays for dye-sensitized solar cells. Issue 22 (11th March 2015) - Kang, Xiaohui; Jia, Chunyang; Wan, Zhongquan; Zhuang, Jia; Feng, Juan
<x xml:space="preserve">Abstract</x> A novel tri-layered ZnO nanostructure, consisting of ZnO nanowires as the underlayer, small ZnO hierarchical microspheres as the interlayer and large ZnO hierarchical microspheres as the overlayer, was designed and studied as a photoanode for dye-sensitized solar cells.